THE ROLE OF THE SUMMARY IN SAVING OF CONFUSED OBJECTIVES TO SUPPORT LAW ENFORCEMENT IN A CRIMINAL JURISDICTION SYSTEM - Tri Budi Haryoko (Polteknik Ilmu Pemasyarakatan, 2018)
This writing aims to discuss the implementation of the duties and functions of management of confiscated objects and booty of the state in the Class I Semarang Sitemap Storage House. One of the core business of the implementation of the RUPBASAN duties and functions is the function of saving the confiscated objects of the state that have been mandated in. This paper will see if there is a gap gap when the function of rescuing confiscated objects mandated by Law No. 8 of 1981 concerning the Book of Law on Criminal Procedure (KUHAP) and Government Regulation Number 27 of 1983 concerning the Implementation of the Criminal Procedure Code can work well with support and commitment. related law enforcement officials. It was also explained that the storage of confiscated objects and booty of the State in the RUPBASAN aims to guarantee the protection of the safety and security of confiscated objects for the purposes of evidence at the level of investigation, prosecution, and examination in court as well as objects which are otherwise confiscated for the state based on court decisions which has permanent legal force.This paper uses a qualitative approach. The results of the discussion indicate that the implementation of confiscated objects in RUPBASAN is in accordance with the KUHAP mandate. But in its implementation these tasks and functions have not been optimally supported both from internal institutions and related law enforcement institutions.